2014
DOI: 10.1088/0964-1726/23/10/105015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel piezoelectric nitrile copolyimide films for high temperature sensor applications

Abstract: A series of amorphous polyimides and copolyimides that contained nitrile were obtained by a two-step procedure. The first step consisted of a polycondensation reaction of 4,4'-oxydiphtalic anhydride (ODPA) with one or two aromatic diamines, namely 1,3-Bis-2-cyano-3-(3aminophenoxy)phenoxybenzene (diamine 2CN) and 1,3-Bis(3-aminophenoxy)benzene (diamine 0CN). In the second step, a thermal cyclodehydration converted each poly(amic acid) or copoly (amic acid) into their corresponding polyimide films. The piezoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Table 1 summarizes the average fiber diameter and degree of porosity for the different samples. (table 2), which is lower than the one reported in [33] for polymer films. It was reported that the high electric field used to obtain electrospun fibers can lead to polymer chain alignment along the longitudinal direction of the polymer fiber [34], which in turn can influence the glass transition temperature of the polymer, as demonstrated for poly(vinyl alcohol) (PVA) [35].…”
Section: Figure 3 -contrasting
confidence: 53%
See 1 more Smart Citation
“…Table 1 summarizes the average fiber diameter and degree of porosity for the different samples. (table 2), which is lower than the one reported in [33] for polymer films. It was reported that the high electric field used to obtain electrospun fibers can lead to polymer chain alignment along the longitudinal direction of the polymer fiber [34], which in turn can influence the glass transition temperature of the polymer, as demonstrated for poly(vinyl alcohol) (PVA) [35].…”
Section: Figure 3 -contrasting
confidence: 53%
“…Nevertheless, just a slight change from 178 ºC in 0CN and 176 ºC in 2CN from bulk polymer [33] down to 176 ºC and 174 ºC (table 2) in 0CN and 2CN electrospun fibers, respectively, was observed. On the other hand, a strong decrease of T g is observed in the 0CN/2CN (50/50 w/w) copolymer sample, which can be related to polymer chain [35] and amorphous regions confinement [37] in the copolymer due to the different nature of the polymer phases with and without CN-dipolar groups.…”
Section: Figure 3 -mentioning
confidence: 91%
“…They are usually obtained by reaction between the dianhydride ODPA and a 50% mol mixture of two aromatic diamines, namely 1,3-bis-2-cyano-3-(3-aminophenoxy)- phenoxybenzene (diamine 2CN, good piezoelectric behavior) and 1,3-bis(3-aminophenoxy)benzene (diamine 0CN, good mechanical behavior) in a two-step reaction. Extensive information about the synthesis, mechanical and dielectric and properties of these copolyimides can be found in [54,55]. Several test were performed concerning the ME response of such metallic glass/piezopolymer/metallic glass, being metallic glass = Vitrovac 4040 or home-made amorphous ribbons, and piezopolymer = PVDF or the 2,6( β -CN) polyimide or other copolyimides [15,56].…”
Section: Futures Perspectives: Me Laminates For High Temperature Amentioning
confidence: 99%
“…For instance, the operational temperature of piezoelectric PVDF is below 85 °C. 51,52 Above this critical temperature, the piezoelectricity decreases rapidly. To overcome this constraint, polyimides (PIs) were examined.…”
Section: Resultsmentioning
confidence: 99%